Education and Labor Market Participation of Wives in Chakwal District - Gondal, Amtul Hafeez; Yasmeen, Rukhsana (Economic Journal of Nepal, 2011)
Based on the field survey conducted in Chakwal, a district of the Punjab, the study identifies various socio-economic and demographic factors. which influence the labor force participation decision of educated married women. The Probit model has been employed in order to empirically identify the effect of education of currently married women on labor force participation. For this purpose we have used dummy variables for different levels of women education are used. Besides women education, other variables like women age, family structure, household size and household income have also been employed in our analysis. The study finds that the education level of married women, their years of training and husbands’ education are strong and positive determinants of women labor force participation (WLFP) decision. However, monthly household income and household property ownership and labor force participation of husband are significantly and inversely related to it. Among demographic factors, woman’s age. household structure and size also affect the WLFP rate to a greater extent. Key words: Labour market; Women education; India; Chakwal District Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics, Tribhuvan University, Kirtipur, Kathmandu Vol. 30, No.3, July-September, 2007 Page :162-174 Uploaded date: 21 July, 2011